Empirical correlation of uniaxial compressive strength and primary wave velocity of Malaysian granites - Goh Thian Lai, Abdul Ghani Rafek, Ailie Sofyiana Serasa, Norbert, . (2014)
Uniaxial compressive strength (UCS) plays a significant role in influencing the stability of structures such as cut slopes and excavation in rock masses. The rock material parameter of UCS also serves as an input parameter for geomechanical modeling in fracture basement studies. However, uniaxial compressive strength test (UCT), requires sample preparation, together with expensive and destructive laboratory testing and thus the limited rock samples has becomes a disadvantage.